Nicaragua : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2004)
The government has fully complied with all the elements of the fourth floating completion point condition, which calls for the implementation of reforms to develop human capital and social protection. Investment in human capital development represents the second pillar of Nicaragua's Poverty Reduction Strategy Paper (PRSP). The policy and reform conditions for reaching the completion point were met by end-2003, except for one condition pertaining to the divestiture of the generating units of the power utility, for which a waiver is recommended.